University students' perceptions through e-learning implementation during COVID-19 pandemic: Positive or negative features dominate? - Mulyani Mulyani; Fidyati Fidyati; Suryani Suryani; Murnia Suri; Halimatussakdiah Halimatussakdiah (Studies in English Language and Education, 2021)
English language instruction that moves away from offline to online should become the EFL lecturers’ concern for their students’ successful learning outcome. The students must be kept in the lecturers’ mind when they plan and program the instruction. This study aims at investigating the students’ perceptions and preferences on English instruction through e-learning implementation during the COVID-19 pandemic. This research applies a qualitative approach in a descriptive method design by involving 106 English class students from three different higher educations in Aceh, Indonesia. The thematic and comparative analyses are applied in analyzing the data. The findings of the study show that 50% of the students impress negative features concerning the internet network, a high need of internet quotas, the limitation of learning material explanation and absorption, and the social media influences. The study also reveals that 59.6% of positive features dominate the findings associated with the students’ interest in e-learning implementation as a new learning experience/exploration, engagement and enthusiasm, the flexibility of time and place, and the advance of digital technology usage and adaptation. Besides, WhatsApp, Opensimka, Google Classroom, and Google Meet have become the four most preferable e-learning platform among the respondents. It implies that e-learning implementation during the COVID-19 pandemic gives a variety of practical benefits to university students in the virtual English class. Yet, this still requires sufficient mentoring and extra supporting digital tools for the students and the lecturers.